FEATURES TO ENSURE THE COMPETITIVENESS OF REINSURANCE OPERATIONS OF THE CEDENT AND THE REINSURER IN THE DOMESTIC AND INTERNATIONAL INSURANCE MARKET - V. Veretnov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Cost-effectiveness of reinsurance operations significantly affect the competitiveness of the cedent and the reinsurer. At the same time, ensuring the competitiveness of reinsurance operations does not always lead to the economic efficiency of the cedent and the reinsurer. We give the definition of the concept of competitiveness of reinsurance operations. The features ensuring the competitiveness of reinsurance operations of the cedent and the reinsurer in the domestic and international insurance market. The use of these features allows you to not only improve the quality of reinsurance protection, which has a beneficial effect on the financial stability of the cedent, but provides such necessary, confidential professional and personal relationship of the cedent and the reinsurer.